Implementation of Decision-Making Systems Based on a Typical Decisive Element - P. Y. Brancevich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
As large amounts of data are received and accumulated, the need to create automated and automatic decision-making systems for a wide variety of tasks becomes more and more urgent. In the technical field, one of them is technical diagnostics, and in medicine, diagnostics of the human condition. Currently, dozens of computer systems for continuous vibration control and monitoring of complex rotary-type units are in commercial operation, which form time trends for 14 vibration parameters with a time step of 1–8 s for each control point at the operated facility. The functionality of a universal decision-making module is proposed, the input data of which are the parameters and characteristics of the observed object, with the required resulting output decision.